We Radio Indonesia Broadcast Program on YouTube as an Effort to Strengthen Youth Empowerment - Pratamasari, Riza Putri; Achmad, Zainal Abidin (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2024)
This research examines how We Radio Indonesia leverages live-streaming YouTube videos to empower young people. Researchers employ qualitative research methods with a virtual ethnographic approach to analyze their strategies. The findings reveal a multi-pronged approach by We Radio Indonesia. They utilize an edutainment format, blending education and entertainment for engaging content. Additionally, they employ a localized language style familiar to Surabaya youth by combining Indonesian and Javanese. Furthermore, We Radio selects expertise-based broadcasters with backgrounds relevant to the broadcast themes. Finally, they leverage media convergence, utilizing various integrated social media platforms to enhance accessibility, sharing, and repeat broadcasts. The study underscores the power of YouTube as a tool for innovation diffusion. The platform's live streaming and sharing capabilities significantly amplify We Radio's strategies, enabling it to disseminate valuable knowledge and foster youth empowerment effectively. This research contributes to understanding how traditional media can adapt and utilize new platforms to connect with young audiences.